Usability Evaluation for Tourism in Uzbekistan Tourism Website (Case Study on uzbektourism.uz) (Global Scientific Review, 2023)
The usability is recognized as an important quality factor of any modern website. There are 1, 196,298,727 websites in the World as of September 2020. Each website works on different reasons. For instance, tourism websites are considered the most influential travel booking. More and more consumers are booking travel breaks lastminute using their smartphone, with google trends showing a massive 519% increase in travel related searches whereby people are including the phrase “tonight” and “today”. The total number of online travel bookings made each year is around 148,3 million, which generates sales of around $755 billion per annum in 2019. In this paper, usability evaluation for tourism in website is proposed and its use is described. The dynamic nature of the Web poses problems for usability evaluations. Development times are rapid and changes to Web sites occur frequently, often without a chance to re-evaluate the usability of the entire site. New advances in Web developments change user expectations. In order to incorporate usability evaluations into such an environment, we must produce methods that are compatible with the development constraints. We believe that rapid, remote, and automated evaluation techniques are key to ensuring usable Web sites. In this paper, we describe three studies we carried out to explore the feasibility of using modified usability testing methods or nontraditional methods of obtaining information about usability to satisfy our criteria of rapid, remote, and automated evaluation